Financial Behavior and Problems Among College Student in Indonesia: the Role of Financial Knowledge - Susan, Marcellia (International Journal of Engineering and Technology, 2018)
There has been a lot of research on financial literacy that has been done in many countries, but the particular research on the topic has a very high relevance while being conducted in Indonesia, considering the low financial literacy level in Indonesia. The results of national survey on the level of financial literacy in 2016 showed that only 29.66% of Indonesian society has decent financial literacy. This research is conducted with the purpose to illustrate the description of Financial Knowledge, Financial Attitude, Financial Behavior, and Financial Problem of college students in Bandung, West Java, Indonesia. Primary data is used in this study to obtain data on related variables. This research descriptively analyzes financial knowledge, financial attitude, financial behavior, and financial problem of college students. This study also conducted hypothesis testing about the causal relationship between the related variables. Structural Equation Modeling is used to determine the relationship of financial knowledge, financial attitude, financial behavior, and financial problem. The result of this research indicates the effect of financial knowledge to financial attitude and its impact to financial behavior. However, college students' financial behavior has no impact on financial problem.Â Â